EFEKTIFITAS E LEARNING UNTUK MENGOREKSI JAWABAN SISWA PADA SOAL-SOAL MATEMATIKA - Daryono Daryono (UNIVERSITAS SLAMET RIYADI, 2021)
Exercise questions for students aim to determine the understanding level of the material to the student. Students are said understand if they can solve problems with the correct process and answers. Limited time and the number of students sometimes make the teacher unable to correct the answers from their students. Teachers only focus on explaining the material so that assistance is needed to be able to assist teachers in correcting student answers quickly and accurately. Therefore, the authors conducted a study entitled the effectiveness of e learning to assist teachers in correcting student answers to math problems.The purpose of this study is to help teachers in correcting the correctness of student answers quickly, of course with the correct process. The expected outcome target is that teachers are able to use the SinauCBT E Learning application so that it can help speed up correcting student answers to math problems.The application of SinauCBT has a positive and significant effect on students at SMPN 12 Surakarta 2020/2021 with a low correlation value of 0.395. The results of the F test in the third equation show that the F significance value is 0.003